2000
DOI: 10.1111/j.1365-313x.2000.00941.x
|View full text |Cite
|
Sign up to set email alerts
|

Double‐stranded RNA interferes with gene function at the single‐cell level in cereals

Abstract: Summary Double‐stranded RNA (dsRNA) has been shown to specifically interfere with gene function in several organisms including tobacco and the model plant Arabidopsis. Here, we report on rapid and sequence‐specific interference of dsRNA with gene function in cereals. Delivery of cognate dsRNA into single epidermal cells of maize, barley or wheat by particle bombardment interfered with the function of co‐bombarded UidA (GUS) and TaGLP2a::GFP reporter genes. Cognate dsRNA was also found to specifically interfere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 34 publications
1
44
0
Order By: Relevance
“…AB055500]). RNAi is homology dependent, and earlier studies revealed that 90% sequence identity between two nucleotide sequences is sufficient to trigger effective RNA degradation (Schweizer et al, 2000;Le et al, 2006;Chen et al, 2008).…”
Section: Differential Cwinv Deficiency In Tobacco Leaves Caused By Rnmentioning
confidence: 99%
“…AB055500]). RNAi is homology dependent, and earlier studies revealed that 90% sequence identity between two nucleotide sequences is sufficient to trigger effective RNA degradation (Schweizer et al, 2000;Le et al, 2006;Chen et al, 2008).…”
Section: Differential Cwinv Deficiency In Tobacco Leaves Caused By Rnmentioning
confidence: 99%
“…To determine if the contributions of any of the eight candidate effectors to infection related to an ability to suppress host PCD, we took advantage of the observation that transient expression of maize transcription factor genes B-Peru and C1 in barley leads to accumulation of anthocyanins and that this only occurs in intact vacuoles of viable cells (Schweizer et al 2000). To assess effects of silencing the BEC on the fractions of host cells that die during the early stages of infection, we co-bombarded each of the RNAi BEC constructs with the B-Peru/C1-expression plasmid pBC17 and pUbiGUS (as cell-death insensitive marker for transformation efficiency).…”
Section: Bec1011 Interferes With Host Cell Deathmentioning
confidence: 99%
“…For examination of cellular viability after HIGS, we delivered 7 μg per shot of vector pTA30BEC (for BEC silencing) together with 7 μg of the B-Peru/C1-expression plasmid pBC17 (Schweizer et al 2000), for anthocyanin production, and pUbiGUS, as transformation marker, into epidermal cells of barley seedling primary leaves by particle bombardment. Half of the leaves were inoculated 1 day after transformation.…”
Section: Cell-death Assaymentioning
confidence: 99%
“…The earliest report of RNAi in wheat was a single cell based transient RNA-silencing assay using wheat epidermal cells (Schweizer et al 2000). In this study, in vitro synthesized dsRNA was cotransformed through particle bombardment with either the gusA (GUS) reporter gene or with the fusion of a germinlike protein (GLP) and reporter gene green fluorescence protein (GFP) (TaGLP2a::GFP).…”
Section: Early Studies On Wheat Rnaimentioning
confidence: 99%
“…In this study, in vitro synthesized dsRNA was cotransformed through particle bombardment with either the gusA (GUS) reporter gene or with the fusion of a germinlike protein (GLP) and reporter gene green fluorescence protein (GFP) (TaGLP2a::GFP). Through phenotypic analysis, Schweizer et al (2000) showed that dsRNA of GUS, TaGLP2a, and GFP were all able to interfere with their respective target genes in a sequence specific manner. In another transient RNAi study in wheat, Christensen et al (2004) used a hairpin construct to target TaGLP2a (renamed TaGLP4 in this later study) to determine the effect of this gene on plant defense responses.…”
Section: Early Studies On Wheat Rnaimentioning
confidence: 99%